1992
DOI: 10.1037/0022-3514.63.4.553
|View full text |Cite
|
Sign up to set email alerts
|

Role of meaningful subgroups in explaining differences in perceived variability for in-groups and out-groups.

Abstract: Five aspects of the complexity of the knowledge representation of business and engineering majors were examined to see whether these differed by group membership and whether these differences were related to differences in perceived variability. Significantly more subgroups were generated when describing the in-group than the out-group; this difference predicted the relative tendency to see the in-group as more variable, and when controlled for statistically, out-group homogeneity effects were eliminated. Fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
166
1
9

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(189 citation statements)
references
References 23 publications
13
166
1
9
Order By: Relevance
“…This is particularly true for unfamiliar rather than familiar others (see Idson & Mischel, 2001). Similarly, research on group perception suggests that, compared with in-groups, out-groups are described in terms of abstract qualities (Fiedler, Semin, & Finkenauer, 1993;Werkman, Wigboldus, & Semin, 1999) and are perceived as being more homogeneous (Jones, Wood, & Quattrone, 1981;Park & Judd, 1990;Park & Rothbart, 1982), as being less differentiated into subgroups (Brewer & Lui, 1984;Linville, 1982;Park, Ryan, & Judd, 1992), and as possessing more structured, predictable properties (Linville, Fischer, & Yoon, 1996). Together, these lines of research suggest that the various dimensions of psychological distance have a similar effect on level of construal.…”
Section: Implications For Psychological Distancementioning
confidence: 99%
“…This is particularly true for unfamiliar rather than familiar others (see Idson & Mischel, 2001). Similarly, research on group perception suggests that, compared with in-groups, out-groups are described in terms of abstract qualities (Fiedler, Semin, & Finkenauer, 1993;Werkman, Wigboldus, & Semin, 1999) and are perceived as being more homogeneous (Jones, Wood, & Quattrone, 1981;Park & Judd, 1990;Park & Rothbart, 1982), as being less differentiated into subgroups (Brewer & Lui, 1984;Linville, 1982;Park, Ryan, & Judd, 1992), and as possessing more structured, predictable properties (Linville, Fischer, & Yoon, 1996). Together, these lines of research suggest that the various dimensions of psychological distance have a similar effect on level of construal.…”
Section: Implications For Psychological Distancementioning
confidence: 99%
“…Similarly, Libby and Eibach (2002, Study 4) found that imagining performing an activity from a third-person perspective produced more abstract, less detailed reports than imagining the same activity from a first-person perspective. Finally, research on group perception suggests that compared with ingroups, outgroups are described in terms of abstract qualities (Fiedler, Semin, & Finkenauer, 1993;Werkman, Wigboldus, & Semin, 1999) and are perceived as more homogeneous (Jones, Wood, & Quattrone, 1981;Park & Judd, 1990;Park & Rothbart, 1982), less differentiated into subgroups (Brewer & Lui, 1984;Linville, 1982;Park, Ryan, & Judd, 1992), and as possessing more structured, predictable properties (Linville, Fischer, & Yoon, 1996).…”
mentioning
confidence: 99%
“…This is not because people are somehow more strongly offended by outgroup members' transgressions than by ingroup members' transgressions, on the contrary, because negative ingroup deviants threaten the positive distinctiveness of the ingroup, they are often judged more harshly than comparable outgroup deviants (Marques, Yzerbyt, & Leyens, 1988;Marques & Paez, 1994). However, ingroup stereotypes are more complex than outgroup stereotypes, and typically contain a number of subtypes to capture the deviant's behaviour without causing modification of the stereotype in general (Park et al, 1992;Richards & Hewstone, 2001). In the event that no such subtype exists, the general motivation to preserve the positive distinctiveness of the ingroup causes group members to mentally exclude the negative deviant from their group, classifying him or her as atypical and exceptional (Castano et al, 2002;Hutchison & Abrams, 2003).…”
Section: Discussionmentioning
confidence: 89%